1995
DOI: 10.1590/s0074-02761995000400004
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis in a low prevalence area: incomplete urbanization increasing risk of infection in Paracambi, RJ, Brazil

Abstract: The risk of schistosomiasis infection and heavy infection in the locality of Sabugo was evaluated in relation to housing in areas with different urbanization development and to residential supply with snail-infested water. Critical sanitary conditions were found in areas of incomplete urbanization, where healthy water supply sources were scarce, and draining of sewage, without previous treatment, was made directly to the water-bodies used for domestic and leisure activities, despite being Biomphalaria tenagoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
2
8
1
1
Order By: Relevance
“…The authors concluded that over the years, it remained as a low prevalence area (Igreja et al 2010). Other areas in the Rio de Janeiro State, also presented low infection levels reached and maintained by Nectomys squamipes rodents (Soares et al 1995).…”
Section: 1mentioning
confidence: 98%
“…The authors concluded that over the years, it remained as a low prevalence area (Igreja et al 2010). Other areas in the Rio de Janeiro State, also presented low infection levels reached and maintained by Nectomys squamipes rodents (Soares et al 1995).…”
Section: 1mentioning
confidence: 98%
“…In many favelas, rapid urban growth overtakes infrastructure development and is characterised by a lack of safe water supplies and sewage systems; such growth is also associated with an increased risk of schistosomiasis exposure (Soares et al 1995, Schall & Diniz 2001, Massara et al 2004. The tendency of Biomphalaria tenagophila and possibly other snail species to cluster in urban neighbourhoods that have high levels of organic pollution in surface water (Teles 2005) increases the risk of transmission in these neighbourhoods.…”
Section: A Typology Of Population Movementsmentioning
confidence: 99%
“…Out of 19 snails, 3 (15.8%) were infected, representing a high infection rate. Soares et al (1995) showed that an incomplete urbanization process due to poverty, lack of information and, above all, the conditions of a destitute urban community may favour the transmission of S. mansoni, possibly causing more harm than in rural environments.…”
Section: Snail Surveymentioning
confidence: 99%
“…This incomplete urbanization process was creating favourable conditions for the transmission of schistosomiasis in some areas of the village. Soares et al (1995) concluded that such a scenario could increase the intensity of infections, and that the low prevalence could mask a highly focal transmission in the village of Sabugo.…”
Section: Introductionmentioning
confidence: 99%